Prevalence and pattern of violence in pregnancy in Ibadan, South-west, Nigeria (2011)
Violence against women is embedded in most cultures with pregnancy associated with higher rates. This study assessed the pattern of violence in pregnancy in two maternity centres in Ibadan, Nigeria. This was a cross-sectional study of antenatal clinic attendees, between 1 and 31 March, 2007 at the University College Hospital (UCH) and the Adeoyo Maternity (AMH). By systematic random sampling, 404 women were interviewed. Analysis was done by means, x(2)-test (at 5% level of significance) and logistic regression. At UCH and AMH, 156 (38.7%) and 248 (61.3%) were studied, respectively. The prevalence of abuse was 17.1% (69 women). The perpetrator was most often an intimate partner (48, 66.1%). The commonest act of violence was a threat of abuse (23, 33.3%). The most frequent reason for the abuse was demand for money. Women in polygamous unions (p=0.035), attending Adeoyo hospital (p=0.00) or with secondary school or less education (p=0.004) had higher levels of abuse. Regression analysis revealed women attending AMH were 3.6 times more likely to be abused (95% CI for OR=1.69–7.81). Violence is not uncommon in this population. Education and employment may reduce these acts.